Monitoring spatial distribution of commercial rattans and palms in the tropical forest of Baratang Islands (Andaman and Nicobar Islands) - Nagabhatla, Nidhi; Roy, P.S.; Jagdale, R. (2007)
Tropical forests are diverse and highly productive of all existing ecosystems. The need of the hour is to protect them from the devastating effect of development. The initiative requires not only assessment of the change in vegetation pattern over years but continuous monitoring of associated diversity as well. Since, the extraction activities in the islands are under check in the existing management policies, the economic upliftment has switched over to the non-forest timber products (NNTP's) (mainly canes and bamboos). The study proposes to foreground the islands having maximum cane diversity and have spotlight a comparative account of distribution in different parts of Andaman & Nicobar Islands. The potential use of remote sensing is highly promising and the study is an approach for multidisciplinary assessments. The study is carried out in the tropical forests of Baratang Forest Division, Andaman Islands for the estimation of rattan and cane resources. The study has aimed to highlight the areas having dense growth of NTPF's using spatial analysis. Distribution pattern of Licula peltata, a palm of high commercial importance has also been analysed. It also attempts to prepare map for the region highlighting areas of high rattan diversity using IRS IC LISS-III data. The necessary set of attributes at a resolution sufficient for monitoring the distribution of rattan species in the islands is also described. A vegetation cover type map was prepared and the ground details were integrated to establish a correlation between the upper storey and the under storey forms.